PENDAMPINGAN PROSES PRODUK HALAL DAN AKUNTANSI USAHA PADA KELOMPOK USAHA NASYIAH SIDOARJO - Nur Ravita Hanun; Hadiah Fitriyah; Lukman Hudi; Surya Ningrum; Eva Hidayatul Khusnah (Jurnal Abdimas Bina Bangsa, 2023)
Nasyiatul Aisyiyah Sidoarjo East Java has a positive activity that accommodates nasyiah cadres who have businesses, especially in the field of food and beverages. The food and beverage products produced are quite varied ranging from fruit salads, wet cakes, pastries, date milk, sinom etc. Unfortunately, there are several problems they face, including, products that have not been certified halal and melum do business financial records. Moreover, since Covid 19 entered Indonesia, sales of partner products have decreased. Through community service from the University of Muhammadiyah Sidoarjo, several activity programs have been carried out, namely: through the nasyiah business group, there will be an increase in the productivity of economic activities for the nasyiah business group by assisting the halal product process and business financial training. So that for the sustainability of the community service program, synergy between academics, Amal Usaha Muhammadiyah, and all elements of society is needed to maximize the existing potential. This target of community service is to improve community governance, human resources, resource managers